INFRINGEMENT OF FAMOUS BRAND RIGHTS IN E-COMMERCE ON TOKOPEDIA - Kristiani, Verlia; Gultom, Elfrida Ratnawati (Universitas Labuhanbatu, 2023)
Well-known brand rights abuses are a common problem in the business world. One form of improvement in business. Which is where the brand is. In addition, the brand provides a sign to distinguish the services and products that one company has toward other company products and to add to the value that company products have good qualities. However, the popularity of popular brands is often exploited by some businesses that sell their product by passing it off through a further electronic trading platform called e-commerce. Next up are several e-commerce platforms which are no shoppee, lazada, pedia. As for the positive laws governing the enforcement of intellectual property rights in the electronic trade as stated in the 2008 bill no. 11 on information and electronic transactions that were then amended into act no.19 in 2016. In practice one of Daniel wallington's handwritten brands was developed by several adpeds. Thus, the author has the research objective of knowing the application of the law to the perpetrator of the famous brand Daniel Wellington offense in e-commerce on the software platform. Then the study is done with a normative type of legal research with a descriptive approach. Describe something that happened and how it worked out.Keywords: Infringement, Marks, E-Commece